MYCOLICIBACTERIUM FORTUITUM INFECTION IN EX SITU EMERALD TREE BOA (Corallus batesii) - Gonzaga, Cássia Regina Ramos (2024)
Emerald tree boas (Corallus batesii) are boids that in situ occurs in forested habitats in the Amazon Basin. The mycobacterial species can infect reptiles but the species Mycolicibacterium fortuitum was identified only in feces samples of ex situ Python regius and was isolated from granulomatous lesions of an ex situ Iguana iguana when was still part of the genus Mycobacterium. This article aims to report a mycobacteria infection case in a female Corallus batesii kept under human care. The animal presented apathy and 2 months of anorexia, being found dead. The necropsy revealed presence of tracheal and pulmonary nodules besides multifocal, bacterial, granulomatous pneumonia. After Fite-Faraco histochemical staining, immunohistochemistry, semi-nested polymerase chain reaction (PCR) and genetic sequencing the Mycolicibacterium fortuitum complex was diagnosed with 99.54% of nucleotide similarity. This mycobacterial species was already pointed out as an important nosocomial pathogen and more studies are necessary to explore their zoonotic potential.